The demand for voluntary carbon sequestration: Experimental evidence from a reforestation project in Germany - Lara Bartels; Martin Kesternich; Andreas Löschel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
With the increasing recognition of the use of reforestation measures as a complement to conventional carbon emissions avoidance technologies it is important to understand the market valuation of local forest carbon sinks for climate change mitigation. We conducted a framed-field experiment among a Germany-wide sample to provide a revealed preference study on the individual willingness to pay (WTP) for carbon sequestration through forests. Our particular focus is on the role of local co-benefits of climate protection activities. In addition, we add geo-data to our experimental data to analyze the impact of spatial variation on the individual WTP. We find that the WTP for carbon removal exceeds the WTP for mitigation efforts found in previous studies. While spatial distances does affect the likelihood to contribute to a local carbon sink, it does not affect the average amount given. Additional survey data finds that trust in forest measures is higher compared to mitigation via an emissions trading scheme, whichcould explain the comparably high WTP.
Keywords: Q51; Q54; C93; Q23; H41; 330; voluntary provision of environmental public goods; climate change mitigation; carbon sequestration; willingness to pay; co-benefits; revealed preferences; framed-field experiment